Incidencias de las tics en el rendimiento escolar en las estudiantes de la escuela Sulima García Valarezo de la ciudad de Machala, periodo escolar 2012 – 2013. - Conza Ramos, Mariana de Jesús (2016)
Talking of basic education is to train students in developing their skills, in order to study personal and social being immersed in the educational process training that teachers apply. Basic education is the space where the school-planned mind develops the capabilities of the student seeking a comprehensive education thereof.